KLASIFIKASI DATA PENJUALAN UNTUK MEMPREDIKSI TINGKAT PENJUALAN PRODUK MENGGUNAKAN METODE DECISION TREE - Demira Intan Suranda; Adi Nugroho (Politeknik Bisnis Indonesia, 2024)
A mature strategy is one of the keys so that a company can increase sales effectively and consistently. With recorded and accurate information, companies can make decisions quickly to predict what supplies consumers will need for the future. Aruna Boutique sells various types of Muslim clothing such as robes and headscarves with several brands of each type. The aim of this research is to determine the sales of the best-selling and least-selling products using the Decision Tree method with the ID3 algorithm. The tool used is a rapid miner using boutique sales transaction data from July - September. The results obtained in this research are the best-selling products Gamis 2 (Umama), veil 2 (DYN) and the less popular products Gamis 1 (Mahdani), veil 3 (Azara) with an accuracy value of 88.24%, which means that the method used it's good enough. Based on the rules obtained, information can be used to increase sales in terms of stock inventory, display and promotion strategies.